Online sources of information on Ukraine’s foreign trade with the European Union - Totska, Olesia Leontiivna (Полтавський державний аграрний університет, 2025)
Statistical data on Ukraine's foreign trade with the EU, which are available on the websites of the State Statistics Service of Ukraine, the State Customs Service of Ukraine, Eurostat, and the Office for the Development of Entrepreneurship and Export, are described.
Keywords: online sources; foreign trade; Ukraine; European Union